Social and Emotional Development Among Gifted Students: Enhancing Decision Making Skills and Resilience - Nor Hamizah Ab Razak; Abdul Rashid Abdul Aziz; Siti Nubailah Mohd Yusof (Human Resource Management Academic Research Society, 2024)
Indexed by ERA